Harveyville, Wabaunsee County - Sage, Abby (Kansas State University, The Chapman Center for Rural Studies, 2011)
Even though Harveyville is considered a “Lost Town,” the community keeps the town going. Without the citizens taking pride and trying to promote the town, Harveyville would probably be a ghost town after the schools were consolidated. Harveyville is a quiet, small town in the southeast corner of Wabaunsee County that is welcoming to all that visit their community.
Abby Sage, “Harveyville, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/46.
Keywords: Dr. Youngman; General Lewis Walt; Harveyville; Mission Valley; School; Wabaunsee County